THE THE RELATIONSHIP BETWEEN SHYNESS AND SELF-ESTEEM WITH LONELINESS IN SOCIAL MEDIA BASED ROLEPLAYER : HUBUNGAN ANTARA SHYNESS DAN SELF-ESTEEM DENGAN LONELINESS PADA ROLEPLAYER BERBASIS MEDIA SOSIAL - Fajar Kawuryan; Dhevi Sa'idatur Rofi'ati (SOSIOEDUKASI, 2026)
This study aims to examine the relationship between shyness and self-esteem with loneliness among social media-based roleplayers. This research employed a quantitative correlational design involving 110 participants aged 15–24 years who were actively engaged in roleplaying activities on social media. Data were collected using psychological scales measuring shyness, self-esteem, and loneliness, and were analyzed using correlation and multiple regression analysis with IBM SPSS 25. The results showed that shyness and self-esteem simultaneously have a significant relationship with loneliness (R = 0.766, R² = 0.587, p < 0.01), indicating a combined contribution of 58.7%. Furthermore, shyness was found to have a significant positive correlation with loneliness (r = 0.721, p < 0.01), while self-esteem showed a significant negative correlation with loneliness (r = -0.669, p < 0.01). These findings suggest that psychological factors such as shyness and self-esteem play an important role in shaping loneliness among social media roleplayers. The study highlights that individuals who experience higher social discomfort and lower self-evaluation tend to be more vulnerable to loneliness in online interaction contexts.